The Inhibitory Properties of the Single-Chain 2S Albumin Seed Storage Protein from Theobroma cacao - Karim, Norzulaiha Abd.; Budiman, Cahyo; Awang, Azwan; Rodrigues, Kenneth F. (Akta Agrosia, 2025)
2S albumin seed storage proteins from Theobroma cacao (Tc-2S) are known for their roles in plant defense mechanisms due to their antimicrobial properties. However, it remains unclear whether both the light and heavy chains of Tc-2S are required for this activity. This study develops an expression system for the single-chain precursor of Tc-2S and evaluate its antimicrobial activity. Specifically, the heavy-chain subunit (Tc-9M), corresponding to residues 78 to 150 of the Tc-2S precursor, was cloned and expressed in a heterologous system. The resulting Tc-9M protein, expressed as a fully soluble protein, was purified via column chromatography, yielding 24 mg of pure protein from 300 mL of the expression culture. Antibacterial and antifungal activity was assessed using the Kirby-Bauer disc diffusion method, revealing that Tc-9M remarkably inhibited the growth of several bacterial strains, including Salmonella sp., Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, and Bacillus cereus. Additionally, Tc-9M inhibited the growth of the yeasts Saccharomyces cerevisiae and Pichia pastoris but showed no activity against the fungus Trichoderma asperellum. These findings ndicate that the single-chain Tc-2S may be sufficient for antimicrobial defense in plants. Because the characterization of the Tc-9M protein has not been previously reported, this work provides a basis for further exploration of the biological significance of the 2S albumin subunit in plant defense.  Keywords: 2S albumin protein, antibacterial, antifungal, heavy-chain peptide, Theobroma cacao